2017
DOI: 10.1080/17436753.2017.1358503
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure, microstructure, thermal expansion and electrical conductivity of CeO2–ZrO2 solid solution

Abstract: CeO 2 -ZrO 2 solid solution was synthesised by mechanical activation solid-state chemical reaction method and characterised by X-ray diffraction (XRD), scanning electron microscopy (SEM), thermal dilatometer, Hebb-Wagner method and DC van der Pauw method. The effects of CeO 2 content on the crystal structure, microstructure, thermal expansion coefficient (TEC), electronic conductivity and total conductivity were investigated. XRD analysis showed that (25 and 75 mol-%) CeO 2 -ZrO 2 solid solutions corresponded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Increase in corresponding coefficients was also reported for CeO 2 -ZrO 2 solid solution upon the introduction of cerium ions. 19 This behavior was explained by reduced strength in Zr-O bonding due to the substitution of larger Ce 4+ for smaller Zr 4+ in the host ZrO 2 lattice (ionic radii of 0.97 vs. 0.84 Å, respectively, in eightfold coordination 20 ). The Zr-O bonds with reduced energy are more affected by temperature increase with resulting increase in CLTEs.…”
Section: Resultsmentioning
confidence: 99%
“…Increase in corresponding coefficients was also reported for CeO 2 -ZrO 2 solid solution upon the introduction of cerium ions. 19 This behavior was explained by reduced strength in Zr-O bonding due to the substitution of larger Ce 4+ for smaller Zr 4+ in the host ZrO 2 lattice (ionic radii of 0.97 vs. 0.84 Å, respectively, in eightfold coordination 20 ). The Zr-O bonds with reduced energy are more affected by temperature increase with resulting increase in CLTEs.…”
Section: Resultsmentioning
confidence: 99%
“…The CGO-YSZ interdiffusion process results in elemental redistribution and increased 4 resistivity. Several studies have presented the formation of solid solution phase between YSZ and CGO and the ohmic resistant depending on the mixing composition after high temperature sintering [14][15][16][17][18][19][20][21]. Tsoga et al [16] reported that the interdiffusion phenomenon at the CGO-YSZ interface occurs already at 1200 ºC.…”
Section: Introductionmentioning
confidence: 99%
“…As the temperature increases from 1300 ºC to 1550 ºC [14][15][16][17][18][19], the observed solid state reaction and interdiffusion occurring at the CGO-YSZ interface become more serious. Conductivity measurements on the mixed solid solution have been performed at various temperatures [20][21][22]. It was found that the ionic conductivity of the mixed solution phase decreases due to partial substitution of YSZ with CGO, reaching a minimum at the composition of CGO0.5YSZ0.5 and then increasing again to reach that of CGO for complete substitution of CGO for YSZ.…”
Section: Introductionmentioning
confidence: 99%
“…ZrO 2 belongs to the class of high‐temperature oxide ceramics, which exhibit many favourable functions, such as an exceptionally high melting point, excellent chemical inertness, excellent thermal insulating properties and a fracture toughness of 2600 MPa at room temperature . Therefore, it is hypothesized that ZrO 2 whiskers can provide potential reinforcing and toughening whiskers in cermets to enhance the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%